Characteristic anti-inflammatory and antioxidative effects of enzymatic- and acidic- hydrolysed mycelium polysaccharides by Oudemansiella radicata on LPS-induced lung injury. (15th January 2019) - Gao, Zheng; Liu, Xinchao; Wang, Wenshuai; Yang, Qihang; Dong, Yuhan; Xu, Nuo; Zhang, Chen; Song, Xinling; Ren, Zhenzhen; Zhao, Fulan; Zhang, Jianjun; Jia, Le
Highlights: The En-MPS showed potential antioxidation by enhancing the enzyme activities and decreasing the lipid peroxidation. The En-MPS had lung-protection effects by regulating the anti-inflammation response and relieving the serum indexs. The GC, HPGPC, FT-IR and NMR analysis reflected that the bioactivities is related to the superior physical properties. Abstract: The present work investigated the antioxidative, anti-inflammatory and pulmonary protective effects of enzymatic- and acid- hydrolysed mycelia polysaccharides (En-MPS and Ac-MPS) from Oudemansiella radicata on LPS-induced acute lung injury (ALI) mice. The results demonstrated that both En-MPS and Ac-MPS showed potential pulmonary protective effects by decreasing serum levels of hs-CRP and C3, increasing pulmonary enzyme values of SOD, GSH-Px, CAT and the level of T-AOC; reducing the activity of MPO; and down-regulating the contents of MDA and LPO. In addition, the levels of TNF-ɑ, IL-1β, and IL-6 in BALF of mice treated with En-MPS at a dosage of 400 mg/kg/d were significantly lower than those in the ALI mice. The in vitro antioxidant effects also showed that the En-MPS was more effective than Ac-MPS. Furthermore, the physical properties of polysaccharides were also investigated by GC, HPGPC, FT-IR and NMR. These results indicated that both En-MPS and Ac-MPS possessed potent antioxidant and anti-inflammatory activities, which could be used as an ingestible drug in preventing lung injury.